CAR T-Cell-Based gene therapy for cancers: new perspectives, challenges, and clinical developments - Jogalekar, Manasi P.; Rajendran, Ramya Lakshmi; Khan, Fatima; Dmello, Crismita; Gangadaran, Prakash; Ahn, Byeong-Cheol (Frontiers in Immunology, 2022)
Chimeric antigen receptor (CAR)-T cell therapy is a progressive new pillar in immune cell therapy for cancer. It has yielded remarkable clinical responses in patients with B-cell leukemia or lymphoma. Unfortunately, many challenges remain to be addressed to overcome its ineffectiveness in the treatment of other hematological and solidtumor malignancies. The major hurdles of CAR T-cell therapy are the associated severe life-threatening toxicities such as cytokine release syndrome and limited anti-tumor efficacy. In this review, we briefly discuss cancer immunotherapy and the genetic engineering of T cells and, In detail, the current innovations in CAR T-cell strategies to improve efficacy in treating solid tumors and hematologic malignancies. Furthermore, we also discuss the current challenges in CAR T-cell therapy and new CAR T-cell-derived nanovesicle therapy. Finally, strategies to overcome the current clinical challenges associated with CAR T-cell therapy are included as well.